The effect of palm oil fuel ash as partial cement replacement material on concrete toward heat generation - Ainaa Bisyarah, Mohd Yusoff (2015)

(untitled)
Pozzolanic materials are natural or artificial materials produced from combustion of the waste. In Malaysia, the utilization of the pozzolanic materials has been widely used in concrete construction which used as a partial replacement material in concrete. The uses of pozzolanic become increasingly widespread in recent times because of technological, economic and ecological advantages of the material contained on pozzolanic. In this study, Palm Oil Fuel Ash (POFA) was utilized as pozzolanic material in concrete. POFA is byproduct obtained by burning of fibers, shells and empty fruit bunches as fuel in palm oil mill boilers. The original sizes of POFA were passing 63μm. Portland cement Type 1 was partial replaced by 10%, 20% and 30% of POFA by weight of cement used. The behaviors of POFA performance in reducing temperature during hydration, drying shrinkage and compressive strength due to the different percentage of partial cement replacement in concrete. The samples were used to undergo heat test where sample 1 is mixer control which contains 100% PC and another 3 samples containing 10%, 20% and 30% of POFA as a partial replacement from amount of the cement used. From the experiments it was found that samples containing 20 % POFA as partial replacement of cement decreasing temperature compared with 100% PC. Besides that, POFA as a partial replacement of cement not only reduces the amount of temperature rise but also delay the time at which the peak temperature occurs The drying shrinkage test showed that the concrete containing 10% of POFA was much low loss moisture compare with other samples. However, the compressive strength of POFA concrete was much lower that the PC concrete. The results obtained and the observations made clear that the partial replacement of cement by POFA beneficial, especially in the construction of concrete.